Research progress on microRNA-1258 in the development of human cancer - Qian, Mengjia; Xia, Yuke; Zhang, Gong; Yu, Han; Cui, Yiyao (Frontiers in Oncology, 2022)
microRNAs (miRNAs) are small endogenous RNAs composed of 20-22 nucleotides that do not encode proteins, which regulate the expression of downstream genes by targeting the 3' untranslated region of mRNA. Plentiful research has demonstrated that miRNAs participate in the initiation and development of diverse diseases and malignant tumors. miR-1258 exerts great influence on tumors, including tumor growth, distant metastasis, migration, invasion, chemosensitivity, cell glycolysis, apoptosis, and stemness. Interestingly, miR-1258 is a miRNA with explicit functions and has been investigated to act as a tumor suppressor in studies on various types of tumors. With accumulating research on miR-1258, it has been found to be used as a biomarker in the early diagnosis and prognosis prediction of tumor patients. In this review, we outline the development of miR-1258 research, describe its regulatory network, and discuss its roles in cancer. Additionally, we generalize the potential clinical applications of miR-1258. This review offers emerging perspectives and orientations for further comprehending the function of miR-1258 as a diagnostic and prognostic biomarker and potent therapeutic target in cancer.